2018
DOI: 10.1111/echo.14149
|View full text |Cite
|
Sign up to set email alerts
|

Right atrial to left atrial volume index ratio is associated with increased mortality in patients with pulmonary hypertension

Abstract: Background Pulmonary hypertension (PH) is characterized by increased pulmonary vascular resistance leading to right heart failure. Elevated right atrial (RA) pressure reflects right ventricular (RV) pressure overload and is an established risk factor for mortality in PH. We hypothesized that PH patients with an increased ratio of RA to LA volume index (RAVI/LAVI), would have increased mortality. Methods We evaluated the association of RAVI/LAVI with mortality in 124 patients seen at a single academic center's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
1
8
0
2
Order By: Relevance
“…Unfortunately, the routine evaluation of the RV function on transthoracic echocardiogram had been neglected until recently. It has been shown that RAVI/LAVI, a novel index that reflects important inter-atrial interactions and RV dysfunction is associated with poor outcomes in patients with pulmonary hypertension [6]. In present study, we have also shown that RAVI/LAVI is also associated with adverse outcomes in CS.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Unfortunately, the routine evaluation of the RV function on transthoracic echocardiogram had been neglected until recently. It has been shown that RAVI/LAVI, a novel index that reflects important inter-atrial interactions and RV dysfunction is associated with poor outcomes in patients with pulmonary hypertension [6]. In present study, we have also shown that RAVI/LAVI is also associated with adverse outcomes in CS.…”
Section: Discussionsupporting
confidence: 74%
“…Prior studies have shown that an increased RA volume is an independent predictor of adverse outcomes in patients with HF [4,5]. It has also been shown that the ratio of right atrial volume index (RAVI) to left atrial volume index (LAVI), RAVI/LAVI, is associated with adverse outcomes in pulmonary hypertension [6].Therefore, we hypothesized that the RAVI/LAVI, as measured by two dimensional doppler echocardiography, is independently associated with death and LVAD implantation in patients with HF presenting with CS.…”
Section: Introductionmentioning
confidence: 99%
“…We carried out the correlation analysis of the above two variables for these seemingly contradictory results and found no significant correlation between the two variables. The possible explanation is that increased right atrial pressure results in right‐to‐left shunt, but increased right atrial pressure may not only be caused by the degree of preoperative tricuspid regurgitation but also by the insufficient volume of FRV and increased right ventricular ejection resistance 17 …”
Section: Discussionmentioning
confidence: 99%
“…Right atrial volume (RAV) and left atrial volume (LAV) were measured at end-systole, in apical four-chamber view by single plane Simpson method. 6 The ratio is then calculated by dividing both the volumes ( Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%